Thermal Transition Properties of Hoki (Macruronus novaezelandiae) and Ling (Genypterus blacodes) Skin Collagens: Implications for Processing - Hofman, Kathleen Anne (Molecular Diversity Preservation International, 2011)
Hoki (Macruronus novaezelandiae) and ling (Genypterus blacodes) are cold-water fish caught in New Zealand waters. Their skins are a major component of the post-processing waste stream. Valuable products could be developed from the skins, as they are primarily composed of collagen, which has many commercial applications. We prepared acid soluble collagens (ASC) from hoki and ling skins, and analyzed their thermal denaturation properties using a Rapid Visco™ Analyzer. At slower heating rates the denaturation temperature (TD) of hoki and ling collagens decreased. This result is consistent with the model of irreversible rate kinetics for the denaturation of collagen. We determined the effects of solvents that disrupt hydrogen bonding on ASC stability. Increasing concentrations of urea from 0.1 M to 1.0 M and acetic acid from 0.1 M to 0.5 M decreased TD. This resulted from the effects of these reagents on the hydrogen bonds that stabilize the collagen triple helix.